The Effect of Women's Presence in Corporate Governance on Financial Distress in Manufacturing Companies Listed on The Indonesia Sharia Stock Index (ISSI) - Noorsy Mubarakh; Setiawan Setiawan; Ira Novianty (Journal Research of Social Science, Economics, and Management, 2026)
This study examined the effect of women’s representation in four corporate governance organs, namely Women on the Board of Directors (WBD), Women on the Board of Commissioners (WBC), Women on the Independent Board of Commissioners (WBIC), and Women on the Audit Committee (WAC), on financial distress, as measured by the Modified Altman Z-Score. A quantitative approach using panel data regression was applied to 97 manufacturing companies consistently listed on the Indonesia Sharia Stock Index (ISSI) during the 2015–2024 period, resulting in 970 observations selected through purposive sampling. Model selection using the Chow test, Hausman test, and Lagrange Multiplier test indicated that the Random Effects Model (REM) with White cross-section standard errors was the most appropriate estimation model. At the 5% significance level, WBD, WBC, and WAC had no significant effects on the Altman Z-Score, whereas WBIC had a significant negative effect (coefficient = ?1.017942; p = 0.0022). Simultaneously, the four independent variables had a significant effect on financial distress (F-statistic = 4.321012; p = 0.001808), although the Adjusted R-squared value was only 1.35%. These findings indicate that the effectiveness of corporate governance cannot be evaluated based on a single supervisory organ but rather depends on the synergy among all governance mechanisms. Furthermore, gender diversity alone does not consistently improve corporate financial performance without being supported by board members’ competence, experience, and independence.